131I-Evans blue: evaluation of necrosis targeting property and preliminary assessment of the mechanism in animal models - Qiaomei Jin; Xin Shan; Qi Luo; Dongjian Zhang; Yuanyu Zhao; Nan Yao; Fei Peng; Dejian Huang; Zhiqi Yin; Wei Liu; Jian Zhang (Elsevier, 2018)
Necrosis is a form of cell death, which is related to various serious diseases such as cardiovascular disease, cancer, and neurodegeneration. Necrosis-avid agents (NAAs) selectively accumulated in the necrotic tissues can be used for imaging and/or therapy of related diseases. The aim of this study was to preliminarily investigate necrosis avidity of 131I-evans blue (131I-EB) and its mechanism. The biodistribution of 131I-EB at 24 h after intravenous administration showed that the radioactivity ratio of necrotic to viable tissue was 3.41 in the liver and 11.82 in the muscle as determined by γ counting in model rats. Autoradiography and histological staining displayed preferential uptake of 131I-EB in necrotic tissues. In vitro nuclear extracts from necrotic cells exhibited 82.3% of the uptake in nuclei at 15 min, as well as 79.2% of the uptake at 2 h after 131I-EB incubation. The DNA binding study demonstrated that evans blue (EB) has strong binding affinity with calf-thymus DNA (CT-DNA) (Ksv=5.08×105 L/(mol/L)). Furthermore, the accumulation of 131I-EB in necrotic muscle was efficiently blocked by an excess amount of unlabeled EB. In conclusion, 131I-EB can not only detect necrosis by binding the DNA released from necrotic cells, but also image necrotic tissues generated from the disease clinically. KEY WORDS: 131I-Evans blue, Necrosis avidity, Radioactivity, DNA binding, Necrosis imaging